Prediksi Laju Pembentukan Air Asam Tambang dengan Metode Column Leaching Test - Muhammad Ramli; Nur Ilham Situru; Muhammad Thamrin (Center of Techonolgy (COT), Fakultas Teknik, Universitas Hasanuddin, 2019)
Prediction of Acid Mine Drainage Forming using Method of Column Leaching Test. One of the environmental problems in coal mining activities is the formation of acid mine drainage. Prediction of the formation of acid mine drainage is important as an effort to control environmental impacts. Acid mine water occurs with interactions between potentially acid-forming material with oxygen, bacteria and water. Objective of study is to analyze the potential for acid mine drainage forming based on material characteristics. The research method was carried out using static and kinetic tests. The static test method classifies materials according to the ability to produce clean acids with observed parameters such as paste pH, total sulfur, Acid Neutralizing Capacity (ANC), Net Acid Generation (NAG), Maximum Potential Acid (MPA), and Net Acid Producing Potential (NAPP). The Kinetic test method predicts the rate of acid-forming of a material. The kinetic test uses the Column Leaching Test Method by using material with composition designed to represent field condition. The kinetic method parameters are pH, electrical conductivity, acidity, alkalinity, sulfate content, and dissolved metal content (Fe, Mn, and Cd). Results of the static test classified the material into NAF Non-Acid Forming (NAF), Potential Acid Forming (PAF) and Uncertain (UC) material categories. The results of the Column Leaching Method classified the material into categories of potential and no potential to form acid mine water. The columns that have the potential to form acid mine drainage occur in columns with large amounts of tonnage of PAF material or those in the upper layer so that it reacts with oxygen. The columns that have no potential to produce acid mine drainage in columns with PAF material are in the middle layer or mixed with NAF material.